Sobre eros na filosofia de Platão: Quatro discursos sobre Amor - Silva, Tiago do Rosário (2022)
This research aims to conduct a study on the theme of Love (Eros) in Plato's philosophy. The Platonic theory of love is not the most widespread in college, although we can speak of its popularization throughout the history of Western thought. Focusing the efforts of writing a doctoral thesis on this subject forces us to point out in the corpus the locus of the content we will use to accomplish it. In this way, we will work on the question of love in Plato's philosophy, starting from a cut of the speeches about love. To do so, we will review the structure of the works in which our theme stands out, namely, the Symposium and the Phaedrus. Plato promotes a kind of conversation among the dialogues, and this can be gauged by the occurrence of a theme in several dialogues. In view of the difficulty of articulating in unitary form what is dispersed in more than one dialogue, it is necessary to investigate to what extent the approximation of two or more distinct dialogues is possible, maintaining the coherence of a unitary understanding in Platonic philosophy. In the Platonic theory of eros it will be equally necessary to investigate the meanings elaborated by these works, of the concepts of philosophy, desire, as well as to evaluate to what extent they can be identified with love. Thus, we have selected Socrates' speech at the Symposium, and Lysias' speeches (the first speech in the dialogue Phaedrus), and Socrates' first and second speeches, also in Phaedrus, as the core points of this research, from which our theme develops.